MUI Fatwa No. 2 of 2002 on Waqf Money: Technological Implementation and Challenges for Waqf Institutions in Indonesia - Nawang Sari, Dewi Azizah (AL-IQTISHAD: Jurnal Ekonomi, 2025)
Cash waqf is one of the instruments of Islamic philanthropy that has great potential in promoting the social and economic development of the ummah in a sustainable manner. The legality of cash waqf in Indonesia is strengthened through MUI Fatwa Number 2 of 2002, which opens up opportunities to manage waqf funds more flexibly and productively. This article examines the implementation of cash waqf in the context of digital technology development, as well as the challenges faced by waqf institutions in carrying out their functions efficiently and accountably. The research method used is descriptive qualitative, with a literature study approach that examines regulatory documents, academic literature, and case studies of waqf institutions. This research aims to provide a comprehensive understanding of the integration of technology in the collection, management, and distribution of cash waqf. The results show that despite constraints such as limited digital infrastructure, low public literacy, and cybersecurity issues, waqf institutions have shown adaptive responses through technological innovation and collaboration. The analysis also reviews the practices of institutions in different regions that have adopted digital platforms. To optimize cash waqf management, progressive policies, multi-stakeholder support, and strengthening the capacity of waqf institutions to face the digital era are required. With the right approach, cash waqf can be a powerful instrument of community empowerment.